Social media activism to reject andesite mining, case of “Wadas Melawan” movement - Arissy Jorgi Sutan (Jurnal Sosiologi Dialektika, 2025)
Social media has become a powerful tool for public discourse, enabling users to engage with social issues. This study focuses on social media activism in the Wadas Melawan movement, which opposes andesite mining in Wadas Village, Purworejo, Central Java. Using a qualitative approach, with the using the primary data of Social Media Data that advocate of case the wadas. This research using Qualitative Data Analysis Software (Q-DAS) as analysis parts specific using NVIVO 12Plus, the data from social media analyse in Nvivo 12Plus using indicators coding and presenting the findings through descriptive figures and tables. Findings reveal three main points: first, social media content centers on resistance, violence, and societal impacts. Second, hashtag analysis shows strong correlations among key hashtags, ranging from 0.5 to 1.0. Third, dominant terms such as #WadasMelawan, “Wadas,” and “warga” (villagers) highlight the central role of the community. While the study is limited to Twitter, it suggests future research should explore other platforms for a more holistic understanding. This research emphasizes how social media amplifies grassroots movements and shapes public narratives, showcasing local digital activism against environmental exploitation unlike prior studies that typically focus on national-level movements.